2014
DOI: 10.4049/jimmunol.1303135
|View full text |Cite
|
Sign up to set email alerts
|

Cell Depletion in Mice That Express Diphtheria Toxin Receptor under the Control of SiglecH Encompasses More Than Plasmacytoid Dendritic Cells

Abstract: Plasmacytoid dendritic cells (pDC) produce type I interferon (IFN-I) in response to viruses and are routinely identified in mice by SiglecH expression. SiglecH is a sialic acid-binding immunoglobulin-like lectin that has an immunomodulatory role during viral infections. Here, we evaluated the impact of SiglecH deficiency on cytokine responses in the presence and absence of pDC. We found that lack of SiglecH enhanced IFN-I responses to viral infection regardless of whether pDC were depleted or not. We also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 40 publications
2
52
1
Order By: Relevance
“…This study reported a greater impact of pDC deletion compared with the two other studies (67, 68), suggesting that pDCs were required for inflammation induced by TLR stimulation and bacterial and viral infections, as well as for controlling both CD4 + T cell responses and CD8 + T cell responses. The discrepancy between these findings and results of other approaches deleting pDCs may derive from the expression of Siglec-H on progenitors that affect other subsets of DCs (70), as discussed below. Thus, deletion of Siglec-H + progenitors would cause a reduction in more than pDCs, and would likely reduce cDC development as well, potentially explaining the relatively larger phenotype reported by these authors.…”
Section: Heterogeneity Of Mature Dendritic Cellsmentioning
confidence: 77%
“…This study reported a greater impact of pDC deletion compared with the two other studies (67, 68), suggesting that pDCs were required for inflammation induced by TLR stimulation and bacterial and viral infections, as well as for controlling both CD4 + T cell responses and CD8 + T cell responses. The discrepancy between these findings and results of other approaches deleting pDCs may derive from the expression of Siglec-H on progenitors that affect other subsets of DCs (70), as discussed below. Thus, deletion of Siglec-H + progenitors would cause a reduction in more than pDCs, and would likely reduce cDC development as well, potentially explaining the relatively larger phenotype reported by these authors.…”
Section: Heterogeneity Of Mature Dendritic Cellsmentioning
confidence: 77%
“…Deletion of SiglecH, the only murine receptor known so far, did not cause overt autoimmune or inflammatory diseases. SiglecH-deficient mice show higher IFN response to murine cytomegalovirus (MCMV), whereas other immune pheno-types in these mice are not pDC-intrinsic (Puttur et al, 2013; Swiecki et al, 2014). We found that Ptprs reduction or DC-specific deletion on Ptprf null background caused mild spontaneous colitis that could be transferred with hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, specialized macrophage subsets in the spleen, lymph nodes and brain also express SIGLEC-H 17,19 . In addition, studies in reporter mice have confirmed Siglech mRNA transcription in progenitor cells 18,20,21 . Mouse pDCs can also express CD8α and, like human pDCs, CD4.…”
Section: Phenotypes Of Human and Mouse Pdcsmentioning
confidence: 93%